Cain and migration: Opportunity amidst punishment? - Snyman, Gerrie 19XX- (HTS teologiese studies, 2019)
In the colonial period since 1492, the colonial masters of Europe sent perpetrators within the colonised territories to other colonies where they became slaves – forced migration and diaspora. These slaves started a new life and became, like Cain’s children, the ancestors of a few notable families (e.g. in South Africa) – a typical postcolonial situation of creating hybrid identities where East met West in Africa to procreate. The question this article asks is the following: how can one link migration and diaspora to Cain’s situation? Cain’s punishment was twofold: the earth would no longer yield to him any fruit, and he would become a fugitive and a wanderer (Gn 4:12). It is as if the first logically led to the second in the Hebrew text. Cain’s vulnerability had a positive effect, so that later on in the story he seemed to have settled and procreated to the extent that his children became founders of arts, science and technology. The LXX partly solves this contradiction by making Cain physically handicapped with trembling and groaning. Significantly, in both traditions he is said to leave the presence of the deity to live elsewhere where he would not be confronted with either the deity or his parents. In both instances, a migration is clearly taking place with the implication that once being branded a perpetrator one can no longer reside within the community or society in whose midst the transgression took place. The perpetrator is removed from the victims and the latter need no longer confront him or her. This article will subsequently consider the following: the value of migration in the biblical text, the significance of Cain moving away from his clan and deity, and the effect of settling elsewhere.